New record of Carnidae (Diptera) from Taiwan and potential challenges in DNA barcode amplification due to pseudogene - Hsuan-Pu Chen; Fang-Tse Chan; Shiuh-Feng Shiao; Ming-Chung Chiu (Biodiversity Data Journal, 2024)
The genus Carnus Nitzsch, 1818 comprises small ectoparasites that feed on the blood of juvenile avians. They are characterised by dealated adults with setose abdominal intersegmental membranes. Carnus orientalis Maa, 1968 was previously recorded in Malaysia and the Ryukyu Islands of Japan, parasitising two owl species: Ketupa ketupu (Horsfield, 1821) and Otus elegans (Cassin, 1852). This study confirms the occurrence of C. orientalis in Taiwan and presents a new host record, along with COI barcode sequences. Additionally, the study also elucidates the difficulties posed by blood meal contamination and pseudogene amplification as confounding factors intrinsic to the molecular taxonomic delineation of C. orientalis via universal DNA barcoding primers.The following new information regarding C. orientalis is provided in this study:Carnus orientalis is first recorded in Taiwan, filling the gap in its East Asian distribution. This is also the first record of Carnidae from Taiwan.Otus lettia (Hodgson, 1836) (Aves, Strigidae) is reported as a new host for C. orientalis, identified on a fallen fledgling.Co-amplification of the host's COI is reported in this study using the universal PCR primer set LCO1490/HCO2198. Additionally, the amplification of a COI-like pseudogene using a newly-designed primer set is detected through abnormal translated amino acid sequences and the occurrence of a stop codon.New specific primers for the COI gene of Carnus were designed in this study.The new distribution and ecological data of C. orientalis enhance our understanding of this species. The provision of new COI primers is anticipated to contribute to future studies employing DNA barcoding in bird-parasitic flies.